La relation éducative : limites et « bonne distance » pour un bien-être partagé dans la classe - Stéphanie Frigout
Since the French Law No. 2013-595 of 8 July 2013, on the direction and planning for reforming the school in the Republic, the use of the term kindness has increased in institutional texts and speeches without allowing professionals to subjectively embrace it. The analysis of clinical research interviews conducted with teachers on this term shows that the issue of real, symbolic or psychological boundaries within the relationship with pupils and their parents arises repeatedly. Drawing on material from these interviews, this article, which follows a psychoanalytically-oriented clinical approach in education sciences, aims to demonstrate the relevance of questioning boundaries in order to reflect on educational relationships before offering group settings that could enable a peaceful and constructive relationship with pupils while respecting "the right distance".